Tracing the 1271-1246 Ma Central Scandinavian Dolerite Group mafic magmatism in Fennoscandia: U-Pb baddeleyite and Hf isotope data on the Moslatt and Borgefjell dolerites - Brander, Linus; Söderlund, Ulf; Bingen, Bernard (Geological Magazine, 2011)
Between 1271 and 1246 Ma, dolerite dykes and sills of the Central Scandinavian Dolerite Group intruded into the Fennoscandian Shield during three distinct magmatic pulses. They are distributed around five large magmatic complexes extending from Sweden to western Finland and record large-scale intracratonic tensional stress. Coeval plutonism is observed in the westernmost terrane of the Sveconorwegian orogen in southern Norway, but differs in the sense of a bimodal character and uncertain Fennoscandian ancestry of the host terrane. We report a U-Pb baddeleyite age of 1269 +/- 12 Ma for a gabbronoritic member of an E-trending set of dykes, called the Moslatt Dolerites, near Lake Vattern in southern Sweden, much farther to the south than any previously known Central Scandinavian Dolerite Group rock. A similar age of approximately 1275 Ma is obtained for a metadolerite sheet in the Borgefjell basement window in the Scandinavian Caledonides in Mid-Norway. The initial epsilon-Hf values for these two dykes are +3.9 and +10.1, respectively, and correspond to the range of values for other occurrences of the Central Scandinavian Dolerite Group (+4.7 to +10.3). They add to the evidence that the Central Scandinavian Dolerite Group is characterized by more positive epsilon values (depleted source) than other mafic Proterozoic suites in Fennoscandia. These results extend the distribution of c. 1270-1245 Ma mafic magmatism in Fennoscandia, particularly when accounting for significant Caledonian shortening. The Central Scandinavian Dolerite Group and coeval bimodal magmatism in S Norway may represent distal magmatic events related to a Mesoproterozoic subduction along the western margin of Fennoscandia rather than hotspot (mantle plume) activity as previously suggested.